Taxonomy of the genus Thyonella (Holothuroidea: Dendrochirotida), with mention of the first record of T. sabanillaensis from the southwestern Atlantic Ocean - Martins, Luciana (Zootaxa, 2018)
The genus Thyonella currently comprises four species which occur in the Atlantic and Pacific Oceans. Thyonella mexicana is the only species known to occur in the Pacific Ocean. The main morphological characters used to distinguish Thyonella species are their dermal ossicles. Since the differences among these characters are subtle, this contribution provides a detailed description and comparison of the ossicle assemblage of the concerned taxa. In addition, description of the internal morphology of three of the concerned species is also provided. Further, this study reports on the first record of Thyonella sabanillaensis for the Southwestern Atlantic. A worldwide revision of the distributional records of Thyonella species is presented and their taxonomy is discussed, concluding that some traditional taxonomic characters should be used cautiously. A brief discussion about the importance of SEM analysis is also provided.